2021
DOI: 10.1128/msystems.00694-21
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biosynthesis of Fatty Acids Is Associated with the Acquisition of Ciprofloxacin Resistance in Edwardsiella tarda

Abstract: Edwardsiella tarda is the causative agent of edwardsiellosis, which imposes huge challenges on clinics and aquaculture. Due to the overuse of antibiotics, the emergence and spread of antibiotic-resistant E. tarda threaten human health and animal farming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 66 publications
0
36
0
Order By: Relevance
“…The potentiation and inhibition were accompanied by the elevation and decreased expression of genes encoding fatty acid biosynthesis, respectively. The association of elevated fatty acid synthesis and antibiotic resistance has been previously reported [26,27,42]; however, the relationship between increased fatty acid biosynthesis and X. oryzae resistance to ZS is a novel finding.…”
Section: Discussionmentioning
confidence: 84%
“…The potentiation and inhibition were accompanied by the elevation and decreased expression of genes encoding fatty acid biosynthesis, respectively. The association of elevated fatty acid synthesis and antibiotic resistance has been previously reported [26,27,42]; however, the relationship between increased fatty acid biosynthesis and X. oryzae resistance to ZS is a novel finding.…”
Section: Discussionmentioning
confidence: 84%
“…The antibiotic bactericidal assay was carried out as previously described ( 32 , 33 ). As mentioned above, after culture in M9 with or without metabolites and/or antibiotics, bacteria were incubated at 37°C with shaking at 200 rpm for 6 h. To determine CFU per ml, 100-μl samples were 10-fold serially diluted and an aliquot of 10 μl of each dilution was spotted onto the LB agar plates and cultured at 37°C for about 11 h. The percent survival was determined by dividing the CFU obtained from the treated sample by the CFU obtained from the control.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the tradeoff in growth seems to be a common phenotype in antibiotic-resistant strains, which may be attributed to the altered metabolism state, as shown in the central carbon metabolism, amino acid metabolism, and energy metabolism. For example, ciprofloxacin-resistant Edwardsiella tarda LTB4-R CIP grew slower than ciprofloxacin-sensitive LTB4-S in the first 8 h, and showed a disrupted pyruvate cycle, decreased energy metabolism, and increased fatty acid biosynthesis [ 15 ]. The absence of nqrA or nqrF in Vibrio alginolyticus increased bacterial resistance to amikacin, gentamicin, and kanamycin, but led to reduced growth in the exponential phase.…”
Section: Discussionmentioning
confidence: 99%
“…A line of evidence has shown that the different metabolic state of the microbes in vivo determines their sensitivity/resistance to antibiotics. For example, the enhanced biosynthesis of fatty acids is associated with the acquisition of ciprofloxacin resistance in Edwardsiella tarda [ 15 ]. In Vibrio alginolyticus , the depressed central carbon and energy metabolisms are associated with the acquisition of levofloxacin resistance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%